(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article provides a legal assessment of the calculation of the loading and unloading fee according to the tariff norms and the purposeless standing of the wagons at the loading and unloading points of general and informal use of the railway transport.